Psychometric Properties of a European French Version of the PTGI. (November 2022) - Henson, Charlotte; Truchot, Didier; Canevello, Amy; Andela, Marie
Purpose: To validate a European French translation of the Posttraumatic Growth Inventory (PTGI). Methods: This study examined the factorial and the convergent validity of the French version of the PTGI (PTGI-F). A first sample of 406 firefighters was used to test the psychometric structure of the PTGI. A second sample of 210 first responders was then used to test its convergent validity. Participants completed measures of growth, traumatic events, PTSD, anxiety and depression, and personality. Results: The PTGI-F was unrelated to Anxiety, supporting the convergent validity of the PTGI-F. Additionally, there was a positive correlation between the PTGI-F and the PCL-C. Finally, the PTGI-F had the same five-factor structure as the PTGI. Discussion: The PTGI-F appears to be a valid tool. However, the contradictions that were put froward by other translated versions suggest that the PTGI should be reconsidered and improved to better assess the growth process.